Comparison of utilization of pressurized automated versus manual hand irrigation during ureteroscopy in the absence of ureteral access sheath. Issue 4 (2nd October 2018) - Doersch, Karen M.; Hart, Kyle D.; Elmekresh, Amr; Milburn, Preston A.; Machen, G. Luke; El Tayeb, Marawan M.
Abstract: This study compared patient outcomes following irrigation applied using an automated pressure system (AP) to hand irrigation utilizing a syringe (HI) during ureteroscopy. Retrospective chart review was performed to evaluate ureteroscopy procedures without a ureteral access sheath. Procedures in which irrigation was applied by AP were compared to those with HI. Statistical analyses included chi-squared tests and Student's t tests. The AP group contained 206 procedures and the HI group, 25. The AP and HI groups were 54.9% and 36% male, respectively. Mean ages were 53.7 ± 18.9 years in the AP group and 44.0 ± 18.5 years in the HI group. Complication rates were 11.2% in the AP and 8.3% in the HI group ( P > 0.99). One stone retrieval failure and one stone recurrence occurred in the HI group; one patient had residual stone in the AP group. No urinary tract infections occurred in the HI group; in the AP group, urinary tract infections occurred in 1.9% of cases. The postoperative pain incidence was equivalent ( P = 0.498). The AP group had one subcapsular hematoma; no calyceal ruptures occurred in either group. In conclusion, irrigation applied by an automated setup appears safe, with similar outcomes to irrigation applied with a handheld syringe.